Effect of systemic and intracortical administration of phenytoin in two genetic models of absence epilepsy - (:unkn) unknown (WILEY, 2006)
1 Spontaneous 7-10 Hz spike-wave discharges (SWDs) are the electroencephalographic hallmark of absence seizures, as can be observed in WAG/Rij as well as in GAERS, two commonly used well-validated genetic rat models of absence epilepsy. A local upregulation of sodium channels within the perioral region of the primary somatosensory cortex indicated an initiation site for SWDs in WAG/Rij rats, in line with a new theory that assumes that SWDs have a cortical focal origin in the perioral region of the somatosensory cortex. We tested whether bilateral microinfusion at this focal site of the sodium channel blocker phenytoin, which is known to aggravate SWDs after systemic administration, reduces SWDs in both models. 2 WAG/Rij rats and GAERS, chronically provided with cortical EEG electrodes and bilateral cortical cannula's, were used. The EEGs were recorded before and after or systemic or bilateral infusion of phenytoin. 3 Microinfusion of phenytoin at the perioral region of the somatosensory cortex produced an immediate cessation of seizure activity in WAG/Rij rats, while systemic injection produced an increase in both genetic models. Microinfusion of the same and higher concentrations of phenytoin in GAERS at the same stereotactic coordinates showed no effect. Phenytoin was effective in GAERS 2mm more posteriorly. 4 The data suggest that both genetic models have a cortical area at which diametrically opposite effects of phenytoin can be found compared to systemic injections: a decrease after local microinfusion and aggravation after systemic administration, although the exact cortical location may be different. Moreover, a deficit in sodium channels might be an ethiological factor underlying an increased probability for the initiation of SWDs in the somatosensory cortex.
Keywords: cortical focus theory; absence epilepsy; GAERS; WAG/Rij; phenytoin; spike-wave discharges; ethosuximide; genetic models; translation research; SPIKE-WAVE DISCHARGES; CELLULAR MECHANISMS; SODIUM-CHANNELS; RAT MODEL; SEIZURES; CORTEX; BRAIN; THALAMUS; NEURONS; DYSREGULATION